2009
DOI: 10.12660/joscmv2n2p72-82
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Study on Reverse Logistic Strategies in the Manufacturing Sector in the Central Area of Cuba

Abstract: The growing need of correct implementation of reverse logistic strategies in the modern company, along with the ignorance of their tendency and behavior in the manufacturing sector in the central area of Cuba, make possible the develop of this study. The main objective is to identify a generic configuration on reverse logistic strategies in manufacturing companies from the Cuban central area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Reverse logistics is a process of transferring used material from the customer to the company to be reused as raw material for producing or recycling products. A previous study by Bernon et al [21] in studying reverse logistics found that there were economic and ecological benefits to the company, and this finding confirmed by Cespón's [22]. Cespón's research was carried out by prioritizing quantitative methods which aimed to test the theory and this made the reverse logistic understanding difficult to explain.…”
Section: Introductionmentioning
confidence: 91%
“…Reverse logistics is a process of transferring used material from the customer to the company to be reused as raw material for producing or recycling products. A previous study by Bernon et al [21] in studying reverse logistics found that there were economic and ecological benefits to the company, and this finding confirmed by Cespón's [22]. Cespón's research was carried out by prioritizing quantitative methods which aimed to test the theory and this made the reverse logistic understanding difficult to explain.…”
Section: Introductionmentioning
confidence: 91%
“…The initial motivation of most electronic manufacturers in conducting RL is recapturing the value from broken or failed products and recovery their assets. Presently they use RL not only for gaining profit but also as a strategy to win the business competition ( Cespon et al., 2009 ). Although recapturing the value of e-waste and recovery assets of used or broken electronic products are also reached, in fact, the motivation of informal e-waste business is gaining profit for survival.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On this basis, they suggested a whole process of "collection, recycling and reuse of products and materials". Cespón, Castro and Lundquist (2009) identified a generic configuration of reverse logistic strategies in manufacturing companies from the Cuban central area. As a result, their research detected the existence of three generic reverse logistic strategies which are: recapturing value, environmental and commercial strategies.in which other manufacturing companies in other countries can adopt.…”
Section: Empirical Review On Reverse Logisticsmentioning
confidence: 99%